2012
DOI: 10.1177/0309324712456646
|View full text |Cite
|
Sign up to set email alerts
|

A traction stress based shear strength definition for fillet welds

Abstract: In this paper, a traction stress based shear strength definition is presented for correlating weldment test data obtained from standard specimens such as those stipulated by AWS B4.0 as well as for applications in general structural design applications when finite element methods are used. With this proposed approach, well-documented discrepancies in shear strength between transverse and longitudinal shear tests can now be reconciled, resulting in a single shear strength value regardless of specimen types and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 11 publications
3
27
0
Order By: Relevance
“…Their results showed that significant shear stress concentration exists at weld ends (at "machined slot" positions in longitudinal shear specimens as shown in Fig. 1a), which can be attributed to typically lower shear strengths in longitudinal shear specimens compared with those in transverse shear specimens, as reported in the literature [15]. However, more test data are needed in order to both validate the findings given by Nie and Dong [15] and develop correction schemes for using Eq.…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…Their results showed that significant shear stress concentration exists at weld ends (at "machined slot" positions in longitudinal shear specimens as shown in Fig. 1a), which can be attributed to typically lower shear strengths in longitudinal shear specimens compared with those in transverse shear specimens, as reported in the literature [15]. However, more test data are needed in order to both validate the findings given by Nie and Dong [15] and develop correction schemes for using Eq.…”
Section: Introductionmentioning
confidence: 65%
“…1a), which can be attributed to typically lower shear strengths in longitudinal shear specimens compared with those in transverse shear specimens, as reported in the literature [15]. However, more test data are needed in order to both validate the findings given by Nie and Dong [15] and develop correction schemes for using Eq. (1) for fillet weld strength characterization.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations